Electronic Legality Of Employment Contracts On Minor Children - Novriyanto Nusi (Universitas Negeri Gorontalo, 2020)
Based on the results of the study, the answers to the existing problems were obtained, that the validity of the employment contract between Youtube and the content creator who was still underage in the statutory provisions contained four conditions for the validity of an agreement, one of which involved the ability to make agreements. Like the real world, there are several requirements from the electronic service provider that must be approved by social media users, especially a content creator. These requirements are commonly known as terms of service. One of the things that are usually regulated in the terms of service is the age of the user so that the legal relationship that exists between the child and the agency or institution is based on the existence of a working relationship between the two parties, in which the child can be represented by the parent or guardian based on a work agreement because children are still unable to carry out legal actions independently, this is because children are categorized as people who are not yet capable of carrying out legal actions As for government regulations regarding employment contracts between YouTube and content creators who are still underage, it can be seen in several laws and regulations in Indonesia which regulate the procedures for engagements or work contracts such as the Civil Code, the ITE Law and in the Manpower Act. For example, in the Civil Code, one of the things that can be used as a reference in the validity of a contract is age, namely 21 years or already married, so based on the problem formulation, the researcher gives an idea in the form of underage content creators who are required to be accompanied or represented by parents or guardians in entering into agreements or contracts with the youtube platform service provider so that it cannot damage the validity of the contract or agreement that has been made by the parties.Keywords: Validity of Employment Contract, Content Creator Children.